(untitled) (Studia Prawnicze / The Legal Studies, 1997)
Z punktu widzenia pożądanego kształtu modelu potencjalnie skutecznego systemu instytucjonalnych gwarancji praw i wolności jednostki polski system wydaje się być zupełny. Po przeanalizowaniu zakresu kompetencji składających się nań instytucji pojawia się jednak spostrzeżenie, czy system ten nie charakteryzuje się jednak większym nasyceniem gwarancjami ochrony konstytucyjności prawa w porównaniu z ochroną praw jednostki w sensie podmiotowym i czy jego konstrukcja nie odzwierciedla tego nastawienia. Wątpliwości te wydają się być zasadne, jeśli wziąć pod uwagę podobne ukształtowanie nowej w polskim prawie instytucji, jaką jest skarga konstytucyjna. From the point of view of the desired shape of the model of a potentially effective system of institutional guarantees of individual rights and freedoms, the Polish system appears to be complete. However, after analysing the scope of competences of the constituent institutions, the observation arises as to whether the system is not nevertheless characterised by a greater saturation of guarantees for the protection of the constitutionality of the law as compared to the protection of individual rights in the subjective sense and whether its design does not reflect this attitude. These doubts appear to be well-founded if one considers the similar formation of a new institution in Polish law, namely the constitutional complaint.